Shattered Minds and Silent Control: Trauma and Power in All Quiet on the Western Front - Saif, Hafsa; Zahid, Maleeha; Sherazi, Nabiha (Annals of Human and Social Sciences, 2025)
This study aims to investigate the horrific experiences of Paul whose initial excitement for war is shattered after seeing the brutal realities of WWI. This paper examines the psychological impact of combat on soldiers. It investigates the way trauma reshapes their emotional state, identity and perception of life. Another significance of this paper is that it explores how the authoritative figures exploit the patriotic sentiments of these individuals by manipulating them for their agendas. It is qualitative research, and the theoretical framework of this research is Chris Brewin’s dual representation theory to analyze the traumatic effects of war on soldiers and Van Dijk’s theory of discourse to explore how institutional power manipulates language and narratives to exert power on their subordinates. This research contributes in the field of trauma studies and literary scholarship. The results of this study is how authoritative people manipulates nation and soldiers to serve their own agendas. Recommendations for future researchers is that they can incorporate the trauma theory to explore the psychological impact of war on soldiers in different cultures. Traumatical effects on soldires due to war can be better understood by the comparative analysis of real life and literary war narratives. Additionally discourse analysis can be done to understand the way politition and media manipulates the nation and soldiers.